(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Apeeling Burger Business (ABB) offers burgers made from banana peel as the main ingredient in the patty instead of meat, catering to health-conscious customers who enjoy delicious food. This burger concept was established in February 2023 and will open in August 2023. It is located at #13 Susano Road, Novaliches Proper, Quezon City, with a capital of Php50,000.00 and five employees. The investment expenditure will be divided among the five owners in a specific ratio. Burgers are a popular option for Filipinos on the go due to their price and convenience. The marketing plan divides Apeeling Burger Business (ABB) 's target market into segments based on demographic, geographic, psychographic, behavioral, and socioeconomic factors. ABB develops business goals and engages with the target market or customer to understand their precise demands. Apeeling Burger Business’ (ABB) co-owners will be their own employees. Apeeling Burger Business’ (ABB) employees are appointed based on their experience with appropriate roles and responsibilities. The results show that providing customers with healthy meals at a reasonable price, a friendly environment, adaptable workers, and social media engagement are all essential to ensuring their contentment. Due to its anticipated favorable financial plan in terms of an income statement, cash flow, and balance sheet, Apeeling Burger Business (ABB) can accomplish its long-term goals and can draw investors.